Patterns of immune-related adverse events in patients treated with immune checkpoint inhibitors: a Brazilian real-world analysis - Santos, Maria Paula Furtado; Pereira, Allan Andersson Lima; Weis, Luiza Nardin; Diniz, Ana Carolina de Aquino; Medeiros, Rodrigo Bovolin de; Katz, Artur; Morbeck, Igor Alexandre Protzner; Fernandes, Gustavo dos Santos; Munhoz, Rodrigo Ramela; Barroso-Sousa, Romualdo (Brazilian Journal of Oncology, 2022)
Objectives: To report real-world data of a cohort of patients treated with immune-checkpoint inhibitors in Brazil, with focus in immune-related adverse events.Material and Methods: In this retrospective study, we analyzed a cohort of patients with metastatic solid tumors treated at an oncology reference center with at least one dose of immune-checkpoint inhibitors (given as monotherapy or in combination with other agents). The safety profile was characterized through the incidence of adverse events, management and hospitalization.Results: We included 185 patients. Immune-related adverse events were observed in 92 of the 185 study patients (49.7%), including 16 patients (8.6%) with such events of grade 3 or 4, and 28 patients (15.1%) requiring systemic corticosteroid therapy. Thyroid disorders (20%), rash (17.8%), pruritus (11.4%) and colitis (11.4%) were the most frequent immune-related adverse events. Five (2.7%) patients discontinued immune-checkpoint inhibitors and 15 (7.0%) were hospitalized due to immune-related adverse events. Development of immune-related adverse events and immune-checkpoint inhibitors used in the firstline setting were associated with prolonged progression-free survival and overall survival in the multivariate analysis. Moreover, age <75 years old and ECOG score 0 or 1 were positively associated with overall survival in the multivariate analysis.Conclusion: This study based upon a Brazilian “real-world” data confirms the toxicity profile of immune-checkpoint inhibitors seen in clinical trials. In accordance with previous retrospective analyses, development of immune-related adverse events was associated with survival outcome of immune-checkpoint inhibitors treatment in patients with metastatic solid cancers.
Keywords: Brazil; Immunotherapy; Immune checkpoint inhibitors; Toxicity